2014
DOI: 10.36510/learnland.v7i2.663
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Teachers for Inclusive Classrooms: Introducing the Individual Direct Experience Approach

Abstract: Inclusion is a contemporary educational movement impacting the role of the classroom teacher. As a result, teacher education programs have made attempts to incorporate inclusive education as part of their curricula. An analysis of the literature reveals that inclusion training has favorable effects on the attitudes of preservice teachers, but has little effect on their perceptions of preparedness to teach in inclusive classrooms. A common complaint is that the focus is heavily weighted on theory, as opposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 25 publications
0
14
0
7
Order By: Relevance
“…Por tal razón, una gran parte de la investigación actual pone énfasis en el impacto de la formación inicial y permanente como factor determinante para la práctica en el aula (Olson & Roberts 2018;Peebles & Mendaglio, 2014;Pegalajar & Colmenero, 2017;Sharma, 2018;Simón et al, 2018) en el ámbito de la inclusión y la diversidad humana (Paz, 2017). Se resalta la necesidad de impulsar programas de formación que preparen al docente para atender a la diversidad de forma más efectiva (Chiner et al, 2015) por medio de la reflexión sobre las barreras de aprendizaje, y generar un clima positivo de aula (Florian & Linklater 2010;Hamre & Oyler, 2004;Pugach et al, 2020).…”
Section: Las Creencias De Los Docentes Sobre La Inclusión Educativaunclassified
“…Por tal razón, una gran parte de la investigación actual pone énfasis en el impacto de la formación inicial y permanente como factor determinante para la práctica en el aula (Olson & Roberts 2018;Peebles & Mendaglio, 2014;Pegalajar & Colmenero, 2017;Sharma, 2018;Simón et al, 2018) en el ámbito de la inclusión y la diversidad humana (Paz, 2017). Se resalta la necesidad de impulsar programas de formación que preparen al docente para atender a la diversidad de forma más efectiva (Chiner et al, 2015) por medio de la reflexión sobre las barreras de aprendizaje, y generar un clima positivo de aula (Florian & Linklater 2010;Hamre & Oyler, 2004;Pugach et al, 2020).…”
Section: Las Creencias De Los Docentes Sobre La Inclusión Educativaunclassified
“…Ao pensar a formação continuada de professores devemos ser levados a ponderar as necessidades formativas dos docentes, oportunizando o diálogo, a troca de experiências e a reflexão sobre a prática. Tais aspectos são apontados como essenciais pela literatura, a qual Research, Society andDevelopment, v. 9, n. 9, e545997818, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i9.7818 recomenda que os cursos de formação continuada na área da educação inclusiva devem considerar cuidadosamente a combinação de estudos, apresentação de atividades práticas baseadas em evidências, além de considerar as necessidades dos docentes ao projetar seus programas (Peebles & Mendaglio, 2014;Brock et al 2014).…”
Section: Considerações Finaisunclassified
“…Dado o exposto, é consenso na literatura nacional e internacional, a urgência e necessidade do desenvolvimento de propostas de atualização e formação continuada, as quais possam auxiliar professores e equipe de apoio pedagógico a exercerem de modo coerente e eficaz o papel para o qual foram formados (Peebles & Mendaglio, 2014). Mais do que somente recursos adaptados, os estudantes com Necessidades Educacionais Especiais (NEE) necessitam de uma equipe que possua formação profissional adequada para os acompanhar (Kassar, 2014).…”
Section: Introductionunclassified
“…One of the qualitative studies included only a focus group (Gustavsen & De Silva, 2013). On the other hand, out of 41 articles, 16 studies focused on practices for implementing the inclusion approach and 11 of those studies were quantitative (Chiner & Cardona, 2013;Duchaine, Jolivette, & Fredrick, 2011;Guo, Sawyer, Justice, & Kaderavek, 2013;Melekoglu, 2014;Mikami et al, 2013;Ogelman & Seçer, 2012;Peebles & Mendaglio, 2014;Pinar & Sucuoglu, 2013;Stanton-Chapman & Brown, 2015;Tremblay, 2013). Whereas, five studies were qualitative research design.…”
Section: Overview Of the Articlesmentioning
confidence: 99%
“…Scholars found that general teachers need to be trained by experts to understand the concept of the inclusion approach(Abu-Heran et al, 2014;Agbenyega & Klibthong, 2014;Ajodhia-Andrews & Frankel, 2010;Duchaine et al, 2011;Lambe, 2011;Mukhopadhyay, 2013;O'Rourke & West, 2015;Vorapanya & Dunlap, 2014). Although, offering sufficient training for teachers who are participated in in inclusive classroom will have positive attitude and high level of self-efficacy for students with special needs(Peebles & Mendaglio, 2014), the training opportunities available to pre-service teachers are few and far between in Australia (O'Rourke & West, 2015). Additionally, Pasha (2012) asserted that there is a lack of professional development for teachers and administrators, which is harmful for inclusive practices in Pakistan.…”
mentioning
confidence: 99%